ANALYSIS OF STUDENTS’ MATHEMATICAL PROBLEM-SOLVING ABILITY ON SIMILARITY MATERIAL VIEWED FROM POLYA’S STAGES AND METACOGNITIVE PROCESSES - Maria Sindi Klaudia Anu; Kristoforus Djawa Djong; Yerum Lapaidemang (Jurnal Prinsip Pendidikan Matematika, 2025)
. This study aims to analyze students' mathematical problem-solving abilities on similarity material based on Polya’s stages and supported by metacognitive processes. This descriptive qualitative study involved three seventh-grade students at UPTD SMPN 6 Kupang Tengah selected purposively based on ability levels: high (SKT), medium (SKS), and low (SKR). Data were collected through mathematical problem-solving tests and semi-structured interviews. The results show that high-ability students (SKT) successfully completed all stages of Polya’s problem-solving steps while demonstrating strong metacognitive regulation, including planning, monitoring, and evaluating their strategies. Medium-ability students (SKS) were able to understand the problem and plan a solution but exhibited weak monitoring and evaluation, leading to errors in executing strategies. Low-ability students (SKR) showed limited conceptual understanding and minimal metacognitive awareness, resulting in difficulties in planning, executing, and reviewing their solutions. These findings highlight that differences in students’ problem-solving performance are strongly influenced by their metacognitive skills and conceptual understanding of proportional relationships. The study emphasizes the need for learning designs that strengthen metacognitive processes and apply differentiated instructional strategies to accommodate students' varying abilities.